2004
DOI: 10.1002/ajmg.a.20613
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of Wolf–Hirschhorn syndrome triggered by a life‐threatening event: Congenital diaphragmatic hernia

Abstract: Wolf-Hirschhorn syndrome (WHS, OMIM 194190) is a chromosomal disorder characterized by retarded mental and physical growth, microcephaly, Greek helmet appearance of the facies, seizures/epilepsy. Closure defects of lip or palate, and cardiac septum defects occur in 30-50% of cases. Its cause is a deletion in the short arm of chromosome 4. We present a male patient, born after 37 weeks gestation, as the fourth pregnancy of non-consanguineous healthy parents, with unilateral cleft lip and palate, hypertelorism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…4J,K). The affected laryngeal cartilage elements in Fgfrl1 -/-mice also provide an explanation for the problems in swallowing and speech development in infants with WHS (Battaglia et al, 2001) and, in combination with the diaphragm phenotype, might contribute to respiratory distress (van Dooren et al, 2004).…”
Section: Skeletal Malformations In Fgfrl1 Null Micementioning
confidence: 99%
See 1 more Smart Citation
“…4J,K). The affected laryngeal cartilage elements in Fgfrl1 -/-mice also provide an explanation for the problems in swallowing and speech development in infants with WHS (Battaglia et al, 2001) and, in combination with the diaphragm phenotype, might contribute to respiratory distress (van Dooren et al, 2004).…”
Section: Skeletal Malformations In Fgfrl1 Null Micementioning
confidence: 99%
“…Laryngeal cartilage elements in Fgfrl1 -/-mice are significantly reduced in size and provide an explanation for the problems in swallowing and speech development in WHS patients. The fully penetrant diaphragm phenotype of Fgfrl1 -/-mutants might underlie the diaphragmatic hernia observed in some WHS patients (van Dooren et al, 2004) …”
Section: Dmmbiologistsorg 288mentioning
confidence: 99%
“…Examples of commonly detected abnormalities include trisomy 18, trisomy 21, trisomy 13, tetrasomy 12p, +der 22 t(11;22), 8p-, and 4p- [Pecile et al, 1990;Howe et al, 1996;Faivre et al, 1998;Lurie, 2003;Borys and Taxy, 2004;Tonks et al, 2004;van Dooren et al, 2004]. A recent excellent review demonstrates numerous "hot spots" that may harbor genes contributing to CDH [Lurie, 2003].…”
Section: Further Evidence That Cdh Has Genetic Determinantsmentioning
confidence: 99%
“…Several studies have suggested that 15q24-26 and 8p23.1 are critical for normal development of the diaphragm since recurrent deletions within these regions were associated with CDH [33][34][35][39][40][41][42] . CDH has also been reported in several cases of monosomy 4p16pter associated with WolfHirschhorn syndrome [43][44][45] . Other candidate regions such as 1q41-q42, 6p22-p25, or 22q11 have also been described [23,36,38] .…”
mentioning
confidence: 95%